The Effect of Sponsorships, Personal Selling and Pricing Strategies on Customer Engagement and Its Impact on Customer Retention of Dental Equipment Industry in Indonesia - Zahari Zahari; Nasir Nasir; Syafruddin Chan (Proceedings of AICS - Social Sciences, 2018)
The purpose of this study is to examine the relationship between Sponsorship, Personal Selling and Pricing Strategies on Customer Engagement, and how it impacts on Customer Retention dental suppliers. Although the dental equipment industry increased 15% per year or equal to USD 1 million, research that discusses dental equipment marketing is very limited. The respondents of this study are the providers of dental health services (dental nurses and dental paramedics) that limit the scope to cover only in Aceh province, Indonesia. Primary data were collected by distributing questionnaires. From 123 questioners distributed, 102 of them filled and returned completely. The data processed by using Smart PLS 2.0, since it able to run factor analysis and regression simultaneously. The results showed that the three exogenous variables: Sponsorship, Personal Selling and Pricing Strategies had a significant positive effect on the mediation variable of Customer Engagement. Only Pricing Strategies had a positive and significant influence on the Customer Retention as a dependent variable. For the mediation test, from the three indirect effect of hypothesis tested, only two of them had the significant indirect effect.Keywords: customer relationship marketing, customer retention, customer engagement, sponsorship, personal selling and pricing strategies.